Kinetic Evaluation of Two-Phase Anaerobic Treatment of Slaughterhouse Wastewater - S. Tanarat (2020)
© Published under licence by IOP Publishing Ltd. Two-phase anaerobic treatment by a continuously stirred tank reactor (CSTR) and an upflow anaerobic sludge blanket (UASB) system was applied to treat slaughterhouse wastewater at ambient temperature, non-pH adjustment, at five different organic loading rates (OLR) of 1.39-2.60 kg COD/m3.d with the hydraulic retention time (HRT) in the range of 14.1-26.4 hr. The kinetic evaluation of the experimental data was carried out using a kinetic model derived from Michaelis-Menten and Monod equation. The maximum substrate utilization rate (kmax) and the half velocity constant (Ks) were 0.252 d-1 and 586.5 mg/l, respectively. The results indicated that the applied kinetic model is capable of explaining the bio-kinetic behaviour of the CSTR-UASB system and can be used as a design criteria for two-phase anaerobic treatment treating other fat-containing wastewater.